2012
DOI: 10.1097/aog.0b013e318242e386
|View full text |Cite
|
Sign up to set email alerts
|

Constipation During Pregnancy

Abstract: A 23-year-old primigravid woman at 14 1/7 weeks of gestation arrived at the emergency department with abdominal pain. Two months earlier, she began having intermittent pain and constipation. She had performed an enema three times and had received intermittent medicated laxatives for 2 months from local clinics. The patient reported having had severe constipation for 7 days 1 year perviously. Her past medical, surgical and family histories were negative. On physical examination, she was 155 cm tall and weighed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The third case demonstrated a patient with progressive colonic distension caused by colonic pseudo-obstruction (Ogilvie’s syndrome). After colonoscopy, radiologic studies showed no evidence of colonic perforation, but the day after colonoscopy the abdominal distension progressed further, the patient went into spontaneous labor and the physicians decided to terminate the pregnancy [ 62 ]. This adverse event could also probably be related to the LGE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third case demonstrated a patient with progressive colonic distension caused by colonic pseudo-obstruction (Ogilvie’s syndrome). After colonoscopy, radiologic studies showed no evidence of colonic perforation, but the day after colonoscopy the abdominal distension progressed further, the patient went into spontaneous labor and the physicians decided to terminate the pregnancy [ 62 ]. This adverse event could also probably be related to the LGE.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these 79 case reports 42 case reports described 51 colonoscopies in 49 patients during pregnancy, distributed equally across the trimesters (21, 16 and 14 colonoscopies in trimester 1, 2 and 3, respectively). Three temporally and etiologically related adverse events occurred in these 49 patients (6.1%), of which 1 occurred in the third trimester [ 85 ] and was possibly related and 2 occurred in the second trimester [ 55 , 62 ] and were probably related to the colonoscopy (see Table 2 and 3 ). Although the evidence level of these case reports is low, these data suggest colonoscopy during pregnancy is probably safe to perform.…”
Section: Discussionmentioning
confidence: 99%